In silico approaches to analyse Acanthus ilicifolius leaves extract as α-glucosidase and α-amylase inhibitors - Yunita Aminatus Sholichah; Naufal Rakha Defransyah; Titik Dwi Sulistiyati; Luthfi Ari Prihanto; Angga Wira Perdana; Hardoko Hardoko; Irenia Paulin Hutapea; Yunita Eka Puspitasari (jurnal1, 2025)
α-glucosidase and α-amylase inhibitors were employed as treatments for type II diabetes. Acarbose, a commonly used commercial medicine for diabetes, has been widely utilized. However, it is associated with gastrointestinal adverse effects.  Hence, the investigation of mangrove plants as potential sources of α-glucosidase and α-amylase inhibitors has garnered significant interest. In Indonesia, the leaves of the Acanthus ilicifolius shrub, commonly known as mangrove, are processed into black and green tea.   Nevertheless, the investigation of phytochemical substances and their potential as antidiabetic agents has not yet been conducted.   Hence, the objective of this study was to determine the phytochemical constituents of the extract obtained from A. ilicifolius mangrove leaves and to evaluate its inhibitory effects on α-glucosidase and α-amylase enzymes using computational methods. The investigations consisted of two steps: the identification of phytochemical substances and the analysis of molecular docking between receptor α-glucosidase (PDB ID: 3A4A) and α-amylase (PDB ID: 4GQR). A. ilicifolius leaf extract contains a variety of phytochemical compounds, including terpenoids (oleanolic acid), steroid (flurandrenolide), flavonoid (corymboside, scutellarin, apigenin 7-O-glucuronide, luteolin, glycitein, apigenin, 4-coumaric acid, were identified in this study. In binding interactions with α-glucosidase, three compounds—reserpine (-10 kcal/mol), scuttelarin (-9.9 kcal/mol), and apigenin-7-glucuronide (-9.9 kcal/mol)—establish a higher energy binding in comparison to the other ligands. Four compounds extracted from the leaves of A. ilicifolius, particularly corymboside, apigenin-7-glucuronide, scutellarin, and oleanolic acid, exhibit greater molecular affinity in their interaction with α-amylase. As a result, it can be deduced that the leaf extract of A. ilicifolius exhibits significant inhibitory activity against α-glucosidase and α-amylase via in silico techniques. As a result, it can be deduced that the leaf extract of A. ilicifolius exhibits significant inhibitory activity against α-glucosidase and α-amylase via in silico methods.